Factors Influencing Decision-making and Outcome in the Surgical Management of Trigeminal Neuralgia - Ammori, Mohannad B.; King, Andrew T.; Siripurapu, Rekha; Herwadkar, Amit V.; Rutherford, Scott A. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives The aim was to optimize the algorithm of operative intervention for trigeminal neuralgia (TN).Design A multivariate analysis was undertaken to determine factors that had influenced both the initial choice of surgical intervention and the subsequent outcomes.Setting The study was undertaken with patients who underwent microvascular decompression (MVD) or percutaneous glycerol injection (PGI) for TN between 2007 and 2009.Participants Seventy-one consecutive patients (43 female) were selected.Main Outcome Measures Data were prospectively recorded and included demographics, etiology, and presentation of TN, duration of symptoms, neurovascular contact, and the outcomes of surgery.Results The response rates for MVD and PGI were 96.2% and 87.5%, respectively. The recurrence rates were 9.8% following MVD and 33.3% following PGI. Multivariate analyses confirmed multiple sclerosis and the identification of neurovascular contact as the only factors predictive of the choice of surgical intervention and the risk of recurrence following MVD.Conclusions Our approach to choosing an operative intervention has been validated. The presence of neurovascular contact and the diagnosis of multiple sclerosis influenced the choice of surgery and were predictive of subsequent outcome. Both MVD and PGI offer effective treatment options for TN. Surgery should be offered early when medical management fails.
Keywords: trigeminal neuralgia; microvascular decompression; percutaneous glycerol injection; neurovascular contact; multiple sclerosis